A Total systems study on Company X - Abarra, Geraldine; De Guzman, Lorie Ann.; De Jesus, Eleanor; Katigbak, Cristel Marie (Diliman, Quezon City College of Engineering, 2003)
Company X is a feed milling company that provides feeds for hods and poultry. It is located in Banay-Banay, Batangas. The competitive advantages or strengths of the company include increasing trend in the retained earnings, large capacity of raw material warehouse, increasing trend of dividends of stock holder, customer loyalty and its growth are the conservative point of view of the management concerning target market and that the company has no marketing strategy. Other weaknesses include excess workers, large capital tied up with raw material inventory and unused machine capacity due to irregular production. The company is currently facing external issues that would affect its operations. The increasing local raw material cuts and the increasing cost of imported raw materials could detriment the supply of the company. Further more, competition is stiff since there is the availability of low cost imported pork and chicken. On the other hand, the increasing demand for hog and poultry feeds and the increasing shift of the backyard raisers to commercial farms are opportunities for the company to expand its market. Given the internal and external factors that would affect the company's operations, SWOT analysis were made to formulate strategies that would help Company X to use its strength and the opportunities in order to counter act its weaknesses and the threats. The new vision-mission of the company is to provide high quality feeds at the lowest possible cost in the shortest possible time to commercial and backyard livestock raisers located ate Banay-Banay, Lipa City and Mataas na Kahoy. Four strategies were recommended in order to attain this goal. The operation strategy of adding a new shift is a short term strategy, which may be implemented in two months. This strategy would benefit the company by increasing its profit by P883,000 per month. Aggressive marketing strategy is proposed in order to get the untapped market. The goal is to be able to sell the new supply of feeds acquired from adding a new shift. If successful marketing were attained, the sales of the company would increase by 100%. The third strategy is long-term, which involve another party: the supplier from Isabela. The plan is to acquire a corn farm in order for the company to satisfy its demand for the said raw material. In the long run, the company may also become a supplier for raw materials to small scale feed milling companies. The issues of worker safety and health hazards were addressed by the waste management strategy. It is recommended the company buy a dust collector. The benefits of this strategy cannot be easily translated to the income statement of the company but may be assessed qualitatively. The installation and implementation of the plan would only take one month but the effects are expected to take the useful life of device.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design
Keywords: Company X; Product management; System design